What can we learn from enterprise architecture models? An experiment comparing models and documents for capability development - Franke, Ulrik; Cohen, Mika; Sigholm, Johan (Software and systems modeling, 2018)
Enterprise architecture (EA) has been established as a discipline to cope with the complex interactions of business operations and technology. Models, i.e., formal descriptions in terms of diagrams and views, are at the heart of the approach. Though it is widely thought that such architecture models can contribute to improved understanding and decision making, this proposition has not rigorously been tested. This article describes an experiment conducted with a real EA model and corresponding real traditional documents, investigating whether the model or the documents lead to better and faster understanding. Understanding is interesting to study, as it is a prerequisite to other EA uses. The subjects ( N = 98 ) were officer cadets, and the experiment was carried out using a comprehensive description of military Close Air Support capability either (1) in the form of a MODAF model or (2) in the form of traditional documents. Based on the results, the model seems to lead to better, though not faster, understanding.